Common law: algumas lições de vinculação para o direito brasileiro - Kersten, Vinicius Mendez (Universidade do Vale do Rio dos Sinos, 2014)
The present study shows some conceptual differences between the two biggest families of law existing in the western - common law and civil law . The research is done through bibliographic search in primary sources of the common law tradition seeking to highlight the key points about the background as well as some peculiarities existing in the United Kingdom and the United States of America about binding precedents. The main point of investigation is the shaping of precedents, overruling and distinguish of them, which implies a search for the origin, definition and operation in its vertical and horizontal binding power. Thus, in addition to the differences between the traditions, the establishment of the judicial careers (judges and lawyers) reveals much about the operation and construction of law. About Brazil the study tries to outline some relevant aspects of its history that contributes to understand the present crisis in / of the Judiciary. In this journey tries to understand the reason for the existence of extraordinary appeal and the problematic organization of the Brazilian federation that concentrates the substantive and procedural legislative powers in charge of the federal government. In this scenario it is important to analyze how the changes introduced by the legislative power are able to solve the problems faced by the judiciary and how the idea of binding implemented here reflect the experience of the common law or has more similarity to the Portuguese tradition. By the end it is proposed a idea of stare decisis that is different from the one that exists here nowadays (binding precedents and jurisprudence condensation), which is closest to the common law tradition, where the ratio decidendi of the decided case provides to further cases the determinants reasons to the decision. The attempt is to see what can be useful, without exaltation of one tradition as better than the other, but rather in understanding the peculiarities that the experience of precedent in common law can help to provide a stare decisis that contributes to a better judicial adjudication with rationalization of access to the judiciary, together with an optimization of the judgments of the courts of superposition to be feasible to have binding judgments – erga omnes – and expansion of the determining reasons of the decisions.
Keywords: Precedentes; Common law; Vinculação; Recurso extraordinário; Precedents; Stare decisis; Extraordinary appeal; ACCNPQ::Ciências Sociais Aplicadas::Direito